Design of Vernis Sprayer Using Macroergonomic Analysis and Design - Anjas Tambunan; Erwin Rozer Sitanggang; Anggianika Mardhatillah (International Journal of Science, Technology & Management, 2020)
The process of spraying varnish is an important part of this industry but it still uses minimal tools so that this process has several obstacles, namely wasted time, unreliable work positions, frequent defects, and disturbed other work stations. To overcome this, a varnish sprayer has been designed, but there are still many things that need to be improved in terms of shape. The research was conducted at SMEs AAT RATTAN CHANDY CRAFT which is engaged in rattan handicrafts such as chairs, tables, serving covers. From the data obtained, 21 out of 28 people experienced complaints in the arms and hands due to less ergonomic work positions and tools. This study uses the Macroergonomic Analysis and Design method, in order to obtain a varnish spray design proposal in the form of a rectangular, faceted iron frame, the main drive of the dynamo (motor), the belt rope as a power connector, the conveyor as a spraying route, the spray gun as a sprayer. The dimensions of this varnish sprayer are 230 cm high, 200 cm wide and 500 cm long. In the proposed working method, there must be two operators, the first operator at the input door of the lifting tool and putting the product on the conveyor, the second operator receiving at the output door of the tool. This eliminates bending and squatting activities because the conveyor height is made as high as 137 cm from the floor surface.